Use of altered informed consent in pragmatic clinical research. (October 2015) - McKinney, Ross E; Beskow, Laura M; Ford, Daniel E; Lantos, John D; McCall, Jonathan; Patrick-Lake, Bray; Pletcher, Mark J; Rath, Brian; Schmidt, Hollie; Weinfurt, Kevin
There are situations in which the requirement to obtain conventional written informed consent can impose significant or even insurmountable barriers to conducting pragmatic clinical research, including some comparative effectiveness studies and cluster-randomized trials. Although certain federal regulations governing research in the United States (45 CFR 46) define circumstances in which any of the required elements may be waived, the same standards apply regardless of whether any single element is to be waived or whether consent is to be waived in its entirety. Using the same threshold for a partial or complete waiver limits the options available to institutional review boards as they seek to optimize a consent process. In this article, we argue that new standards are necessary in order to enable important pragmatic clinical research while at the same time protecting patients' rights and interests.